Performing Music: Shared Concerns - Dunsby, Jonathan (Oxford Clarendon, 1997)
What does it feel like to perform music? Are there aspects of performance that remain mysterious even to the musicians themselves? What elements are open to scrutiny, experiment, and improvement? This book takes a stimulating look at dimensions of music-making that have not previously been considered together. Jonathan Dunsby deals with "performance studies" as a coherent subject, exploring such topics as the relationship between anxiety and artistry, tensions between Romanticism and Modernism, and the sound and design of music. Covering a number of intriguing issues in clear, non-technical language, Performing Music will provide the general reader with vivid insights into how performers think, and what they think about.Frequently Bought Together
Keywords: Performance